2017
DOI: 10.1021/acs.analchem.6b05074
|View full text |Cite
|
Sign up to set email alerts
|

Determination of PAHs in Solution with a Single Reference Standard by a Combination of 1H Quantitative NMR Spectroscopy and Chromatography

Abstract: We have applied a combination of H quantitative NMR spectroscopy (H-qNMR) and chromatography (GC or LC) to establish reliable analytical methods (qNMR/GC and qNMR/LC) for organic compounds. In this method, a reference standard is used as an internal standard for both H-qNMR and chromatography to estimate relative molar sensitivity (RMS) for analytes. The RMS values are calculated from the molar ratios between analytes and the reference standard obtained byH-qNMR; and the response ratio between them obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Recently, NMR spectroscopy has shown great potential in environmental research, since it is able to study liquids, gels, solids, gases, and multiphase samples and produce rapid, reliable, and highly sensitive results [ 10 , 11 , 12 ]. Quantitative NMR spectroscopy can also provide accurate quantitative information about the sample constituents [ 13 ]. Unlike GC, NMR spectroscopy does not require multiple detectors, and it is capable of analyzing mixtures with advanced spectroscopic methods, such as multi-dimensional spectroscopy and diffusion-ordered NMR spectroscopy [ 10 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, NMR spectroscopy has shown great potential in environmental research, since it is able to study liquids, gels, solids, gases, and multiphase samples and produce rapid, reliable, and highly sensitive results [ 10 , 11 , 12 ]. Quantitative NMR spectroscopy can also provide accurate quantitative information about the sample constituents [ 13 ]. Unlike GC, NMR spectroscopy does not require multiple detectors, and it is capable of analyzing mixtures with advanced spectroscopic methods, such as multi-dimensional spectroscopy and diffusion-ordered NMR spectroscopy [ 10 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially crucial in studies using mice, where only small amounts of tissue or biofluids are available or for studies with human tissue material of low availability. In the last years, most metabolomic studies used NMR as a stand-alone technique, however a complimentary approach with MS is becoming increasingly popular, as it improves sensitivity and metabolome coverage (26)(27)(28).…”
Section: Nuclear Magnetic Resonancementioning
confidence: 99%
“…Several studies have reported conventional quantification methods for MIR and its derivatives in PM plants using HPLC 4,10) and in PM dietary supplements using liquid chromatography/tandem mass spetrometry (LC/MS/MS). 11) However, detection of MIR in PM may be difficult owing to its low content and the multiple interfering compounds in crude drugs or other ingredients in products. Additionally, not only analytical standards but also commercial reagent-grade MIR is hardly available for routine analysis.…”
Section: Introductionmentioning
confidence: 99%